European Market Infrastructure Regulation (EMIR) - Pascal Berg (European Institute for Knowledge & Value Management (EIKV), 2016)
Derivatives and especially OTC derivatives1 have become subject of many critics and controversy since the subprime crisis, which fuelled the outbreak of the financial crisis and the collapse of Lehman Brothers end of 2008.2 Vocabulary like derivatives, too big to fail, Credit Default Swaps (CDS), exotic options have come to everybody's mouth and have been widely discussed and despised. The latter sovereign debt crisis even spurred that stance, so that a G20 meeting in Pittsburgh intended to foster the transparency of OTC derivatives markets and brought stricter and tougher regulations to that market. Sovereigns and regulator don't want to end up anymore in a situation, where they are to some extend blackmailed to rescue the financial system due to the moral hazard of the baking industry. According a research publication of the Federal Reserve Bank of Dallas with the topic “Assessing the Costs and Consequences of the 2007 – 2009 Financial Crisis and Its Aftermath”, the research came up in one of its scenarios with a cost of 15 to 30 Trillion USD only for the United States.3 This shows how severe the downtrend and how dramatic the crisis was since the Great depression in 1930. It further underlines the crucial importance to act in order to avoid any future systemic crisis. The paper in hands aims to highlight the regulation which has been especially put in place to tame that opaque market whose interlinkage and dependencies between the banks and the real economy have been so complex and difficult to oversee during the financial crisis...
Keywords: 330